Topical Sphenopalatine Ganglion Block Compared With Epidural Blood Patch for Postdural Puncture Headache Management in Postpartum Patients: A Retrospective Review. Issue 8 (1st November 2018) - Cohen, Shaul; Levin, Danielle; Mellender, Scott; Zhao, Rong; Patel, Preet; Grubb, William; Kiss, Geza
Abstract : Background and Objectives: Postdural puncture headache (PDPH) is a severe and debilitating complication of unintentional dural puncture. The criterion-standard treatment for PDPH has been epidural blood patch (EBP), but it is an invasive intervention with the potential for severe complications, such as meningitis and paralysis. We believe this is the first ever 17-year retrospective chart review in which we compare the effectiveness of sphenopalatine ganglion block (SPGB) to EBP for PDPH treatment in postpartum patients. Methods: We conducted a chart review of the first authors' obstetric patients who experienced PDPH from an unintentional dural puncture from a 17-gauge Tuohy needle for labor epidural from January 1997 to July 2014. Demographic characteristics, headache severity, and associated symptoms were collected prior to treatment. Forty-two patients who received SPGB and 39 patients who received EBP were identified. Residual headache, recovery from associated symptoms, and new treatment complications were compared between the 2 groups at 30 minutes, 1 hour, 24 hours, 48 hours, and 1 week posttreatment. Results: A greater number of patients showed significant relief in their PDPH and associated symptoms at 30 and 60 minutes after treatment with SPGB than after treatment with EBP ( P < 0.01). Only the EBP patients complained of posttreatment complications, which all resolved in 48 hours. Conclusions: A greater number of patients experienced a quicker onset of headache relief, without any new complications, from treatment with SPGB versus EBP. We believe that SPGB is a safe, inexpensive, and well-tolerated treatment. We hope that clinical trials will be conducted in the future that will confirm our findings and allow us to recommend SPGB for PDPH treatment prior to offering patients EBP.